Exploring the Biological Potential of Mountain Germander Polyphenolic Extract on Cellular Model Macromolecules, Human Cell Lines, and Microbiome Representatives - Ana Mandura Jarić; Ksenija Durgo; Ana Huđek Turković; Petra Petek; Andrea Petrinić; Danijela Šeremet; Aleksandra Vojvodić Cebin; Draženka Komes (Applied Sciences)
In the context of revitalizing the use of traditional plant species as remarkable sources of bioactive compounds, the determination of their biological effects is of utmost importance. Among Lamiaceae species, Teucrium montanum (Mountain Germander) represents understudied Mediterranean plant species; it is rich in polyphenols, which are well-studied biologically active compounds for human disease prevention and the reduction of oxidative stress, i.e., phenolic acids, phenylethanoid glycosides, and flavonoids. For that purpose, the aim of this study was to investigate the antioxidant, cytotoxic, and genotoxic effects of Mountain Germander (MG) polyphenolic extract (0.025, 0.050, 0.150, and 0.500 mg extract mL−1) on the hepatocellular (HepG2), tongue (CAL 27), gastric (AGS), and colorectal (Caco-2) continuous human cancer cell lines, as well as its bacteriostatic potential on representative members of human microbiota. In addition, the antioxidant potential of the MG polyphenolic extract was determined using bovine serum album and DNA plasmid as cellular model macromolecules. In vitro analysis revealed a significant cytotoxic effect of all MG extract concentrations on AGS and Caco-2 cell lines after prolonged treatment (24 h). In addition, treatment with 0.500 mg extract mL−1 showed the most pronounced antioxidant effect under prolonged treatment (24 h) on CAL 27 and HepG2 cell lines. All of the applied MG extract concentrations seem to have a genoprotective effect on DNA plasmid. Furthermore, a significant inhibitory effect on E. coli was detected upon the treatment with 0.150 mg extract mL−1, reducing the cell viability by 56%.